Status of multidrug resistant tuberculosis (MDR-TB) among the Sahariya tribe of North Central India - Ravi Prakash; Dilip Kumar; Vinod K. Gupta; Sanjay Jain; Devendra S. Chauhan; Pramod K. Tiwari; Vishwa M. Katoch (Elsevier, 2016)
Summary: Background: The incidence/prevalence of tuberculosis (TB) is reported to be high in the Sahariya tribe of North Central India. The outbreaks of different drug-resistant isolates of Mycobacterium tuberculosis emphasized the need for continuous monitoring of resistance to anti-tuberculosis drugs. This study aimed to assess the profile of multidrug resistant TB among the Sahariya tribe and their non-tribal neighbors for first line drugs through field-based investigations. Methodology: A total of 274 sputum positive pulmonary TB individuals were enrolled and studied for their drug susceptibility profile by the proportion method. Results: A total of 21 cases from Sahariya and 6 from non-tribes were identified with MDR-TB. Thus Sahariya tribe showed a 1.95-fold increased risk of developing drug resistance than non-tribes. Significant differences were observed for developing drug sensitivity between Sahariya males and females when analyzed for resistance developed to any drug and overall drug resistance vs. sensitive isolates, respectively. A 4.46-fold risk was found for MDR-TB among the smokers of Sahariya tribe, whereas, the non-tribes did not show any significant association. Conclusion: The drug susceptibility profile developed in the present study indicates that drug-resistant tuberculosis is emerging as a serious public health concern in Sahariya tribe. Urgent and effective control measures and better management policies are needed for the prevention of MDR-TB in the tribe. Keywords: Sahariya tribe, Mycobacterium tuberculosis, MDR-TB